2016
DOI: 10.3892/etm.2016.3917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the PI3K/AKT signaling pathway on hypoxia-induced proliferation and differentiation of bone marrow-derived mesenchymal stem cells

Abstract: Bone marrow-derived mesenchymal stem cell (BM-MSC) transplantation has been demonstrated to be an effective way of augmenting angiogenesis of ischemic tissue. The low oxygen conditions in ischemic tissue directly affect the biological behavior of engrafted cells. However, to date, the mechanism through which hypoxia regulates self-renewal, differentiation and paracrine function of BM-MSCs remains unclear. Clarification of this mechanism would be beneficial to the use of stem cell-based therapy. The PI3K/AKT pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Inhibition of p38MAPK or Akt also affected BMMSC proliferation, although the suppressive effects of p38MAPK and Akt inhibition on cell proliferation were not critical. Consistently, previous studies have shown that MSCs can repopulate under suppression of ERK , p38MAPK , and Akt .…”
Section: Discussionsupporting
confidence: 90%
“…Inhibition of p38MAPK or Akt also affected BMMSC proliferation, although the suppressive effects of p38MAPK and Akt inhibition on cell proliferation were not critical. Consistently, previous studies have shown that MSCs can repopulate under suppression of ERK , p38MAPK , and Akt .…”
Section: Discussionsupporting
confidence: 90%
“…Several groups have demonstrated that the PI3K/AKT/mTOR and the PI3K/AKT/FOXO3a signaling pathways are associated with MSC survival in culture or animal models . It has also been demonstrated that activation of the PI3K/AKT signaling pathway is critical to increasing hypoxia‐induced proliferation and differentiation of MSCs into ECs …”
Section: Current Strategies Used To Construct the Bone Marrow Niche Imentioning
confidence: 99%
“…Phosphorylated Akt acts on the downstream target factors and plays a role in cell cycle regulation and cell growth. It has been reported that PI3K‐Akt pathway serves an important role in the proliferation of MSCs . However, whether ERK1/2 and PI3K/Akt signalling pathways are involved in the effect of LIPUS on proliferation of hAD‐MSCs are unknown.…”
Section: Introductionmentioning
confidence: 99%